The cost of health workforce gaps and inequitable distribution in the Ghana Health Service: an analysis towards evidence-based health workforce planning and management - James Avoka Asamani; Hamza Ismaila; Anna Plange; Victor Francis Ekey; Abdul-Majeed Ahmed; Margaret Chebere; John Koku Awoonor-Williams; Juliet Nabyonga-Orem (BMC, 2021)
Abstract Background Despite tremendous health workforce efforts which have resulted in increases in the density of physicians, nurses and midwives from 1.07 per 1000 population in 2005 to 2.65 per 1000 population in 2017, Ghana continues to face shortages of health workforce alongside inefficient distribution. The Ministry of Health and its agencies in Ghana used the Workload Indicators of Staffing Needs (WISN) approach to develop staffing norms and standards for all health facilities, which is being used as an operational planning tool for equitable health workforce distribution. Using the nationally agreed staffing norms and standards, the aim of this paper is to quantify the inequitable distribution of health workforce and the associated cost implications. It also reports on how the findings are being used to shape health workforce policy, planning and management. Methods We conducted a health workforce gap analysis for all health facilities of the Ghana Health Service in 2018 in which we compared a nationally agreed evidence-based staffing standard with the prevailing staffing situation to identify need-based gaps and inequitable distribution. The cost of the prevailing staffing levels was also compared with the stipulated standard, and the staffing cost related to inequitable distribution was estimated. Results It was found that the Ghana Health Service needed 105,440 health workers to meet its minimum staffing requirements as at May 2018 vis-à-vis its prevailing staff at post of 61,756 thereby leaving unfilled vacancies of 47,758 (a vacancy rate of 41%) albeit significant variations across geographical regions, levels of service and occupational groups. Of note, the crude equity index showed that in aggregate, the best-staffed region was 2.17 times better off than the worst-staffed region. The estimated cost (comprising basic salaries, market premium and other allowances paid from central government) of meeting the minimum staffing requirements was estimated to be GH¢2,358,346,472 (US$521,758,069) while the current cost of staff at post was GH¢1,424,331,400 (US$315,117,566.37), resulting in a net budgetary deficit of 57% (~ US$295.4 million) to meet the minimum requirement of staffing for primary and secondary health services. Whilst the prevailing staffing expenditure was generally below the required levels, an average of 28% (range 14-50%) across the levels of primary and secondary healthcare was spent on staff deemed to have been inequitably distributed, thus providing scope for rationalisation. We estimate that the net budgetary deficit of meeting the minimum staffing requirement could be drastically reduced by some 30% just by redistributing the inequitably distributed staff. Policy implications Efficiency gains could be made by redistributing the 14,142 staff deemed to be inequitably distributed, thereby narrowing the existing staffing gaps by 30% to 33,616, which could, in turn, be filled by leveraging synergistic strategy of task-sharing and/or new recruitments. The results of the analysis provided insights that have shaped and continue to influence important policy decisions in health workforce planning and management in the Ghana Health Service.